Hubungan Motivasi Orang Tua Terhadap Kemampuan Kognitif Anak Kelompok B Di Ba Aisyiyah IV Sidokerto, Plupuh, Sragen Tahun 2015/2016 - NAFIANA, Fita Nafidah (2016)
This study aims to determine the relationship between motivation and cognitive ability of parents of children in group B in BA Aisyiyah IV Sidokerto, Plupuh, Sragen year 2015/2016. This study was descriptive correlational. The population in this study were 56 children, while the study sample as many as 48 children. The collection of data through observation in the variable cognitive abilities of children and questionnaire on parental motivation variable. Mechanical data analysts use product moment correlation technique. Based on the calculations, r product moment = 0.962 with sifgnifikansi level of 0.000 (p <0.05). From the results of these calculations can be seen that there is a relationship between the motivation of parents For children's cognitive abilities (counting beginning) ingroup B BA Aisyiyah IV Sidokerto, Plupuh, Sragen year 2015/2016.